Sistem Kehadiran Menggunakan Quick Respone Code Dengan Enkripsi Algorithm Message Digest 5 dan Vigenere Cipher Pada SpeedCom IT Consulting - Yudi Wiharto; Ari Irawan (Jurnal SISKOM-KB (Sistem Komputer dan Kecerdasan Buatan), 2018)
The attendance system is a resource that must exist and is needed both by government agencies and private agencies for the onset of an initial operational activity in it. The existence of attendance tools at this time is vital considering the function is able to support activities and implementation of work activities in it so that the tool must exist in an agency. Especially for SpeedCom IT Consulting, data collection and attendance reporting system used so far using data processing applications with web-based internet facilities. This is considered less effective by agencies, because employees can make input attendance wherever and whenever. From the problem it raises the idea of ​​adding an encrypted Quick Respone code (QR Code), in which it can perform management and attendance data collection. Supported with the availability of local internet network within the agency, this application will be used as a medium of attendance and recapitulation of employee attendance every month. With the QR Code is expected no more games or cheating by employees in the process of attendance and is expected also this application will facilitate the administrator in managing the presence of employees in the office so that the results of reporting data can be known easily, quickly and accurately.